(The Study of Production on Aloe Vera Juice - Eddy Sapto Hartanto; Enny Hawani Lubis (Warta Industri Hasil Pertanian, 2002)
A study on aloe vera juice processing has been carried out. stages of treatment include peeling, washing, extraction ,filtration,formulation, bottling pasteurization, sterilization and labeling .the treatment of the formulation were addition of water,cane and non-nutritive sweetener, the equal volume compration between aloe vera and water was the best treatment and preferred by panelist.the best formulation of this research was conducted at PH 3,74 with total solid of 18,02 % sugar conten of 14,675 and benzoat of 521 mg/kg. after 12 weeks storage ,the product showed microbiologically safe and met the indonesia national standard (SNI) of fruit juice.